SmartCT - Development of AI based methods for automation of RoboCT scan procedures - Sukowski, Frank; Rauch, Daniel; Schielein, Richard; Schön, Tobias; Waldyra, Adrian; Fries, Mara; Maier, Andreas; Schneider, Linda-Sophie; Herl, Gabriel; Wittl, Simon; Zabler, Simon; Zeitel, Sebastian; et al. (e-Journal of Nondestructive Testing, 2024)
The SmartCT system consists of AI based methods that assist users of robot-based CT systems (RoboCT) to digitalize industrial parts of almost arbitrary size and geometrical complexity with a high degree of automation. Due to the high number of degrees of freedom and thus complexity, RoboCT scan procedures are difficult to parametrize with respect to collision safety and image quality. The SmartCT assist functions help users to perform measurements quickly and safely while using advanced algorithms for geometrical image correction and 3D-CT volume reconstruction.<br
Keywords: alibration; reconstruction; CT; Trajectory; Scan Planning